Educación familiar en el desarrollo cognitivo de niños con discapacidad intelectual - Posada Salas, Rina Evangelina (2021)
The purpose of this research is to train parents in the cognitive development of children with mild intellectual disability, which has been present in the Third and Fourth Grade of General Basic Education, in the Yasuní Private School, school period 2019-2020. The proposed objective is to analyze the contribution of family education in the cognitive development of children with Mild Intellectual Disability of the basic elementary level. The following were detected: learning deficiencies, parental abandonment, lack of affection, which is shown in their low performance and the constant complaints from teachers about the little or no help from parents in academic reinforcement within the home. The methodology that was applied allowed to obtain direct and adequate information, with a mixed approach supported by a descriptive-explanatory field research, bibliographic and in the theoretical framework with various theoretical references, different instruments were applied such as: surveys and interviews, it was evidenced in legal representatives learning problems within homes, does not reflect help in controlling tasks, in addition, the lack of affectivity towards their children reflected in the inattention, little interest and abandonment of children with mild intellectual disabilities , these factors make family dysfunctionality worse and their performance is low, affecting the teaching-learning process with all this information, a system of workshops was held for legal representatives to provide solutions and support for them to develop skills and thus teach in daily tasks and channel their emotions in their affective part towards their children with mild intellectual disability strengthening cognitive development............